MMP12 knockout prevents weight and muscle loss in tumor-bearing mice - Lingbi Jiang (BMC, 2021)
Abstract Background Colorectal cancer is a malignant gastrointestinal cancer, in which some advanced patients would develop cancer cachexia (CAC). CAC is defined as a multi-factorial syndrome characterized by weight loss and muscle loss (with or without fat mass), leading to progressive dysfunction, thereby increasing morbidity and mortality. ApcMin/+ mice develop spontaneous intestinal adenoma, which provides an established model of colorectal cancer for CAC study. Upon studying the ApcMin/+ mouse model, we observed a marked decrease in weight gain beginning around week 15. Such a reduction in weight gain was rescued when ApcMin/+ mice were crossed with MMP12−/− mice, indicating that MMP12 has a role in age-related ApcMin/+-associated weight loss. As a control, the weight of MMP12−/− mice on a weekly basis, their weight were not significantly different from those of WT mice. Methods ApcMin/+; MMP12−/− mice were obtained by crossing ApcMin/+ mice with MMP12 knockout (MMP12 −/−) mice. Histological scores were assessed using hematoxylin-eosin (H&E) staining. MMP12 expression was confirmed by immunohistochemistry and immunofluorescence staining. ELISA, protein microarrays and quantitative Polymerase Chain Reaction (qPCR) were used to investigate whether tumor could up-regulate IL-6. Cell-based assays and western blot were used to verify the regulatory relationship between IL-6 and MMP12. Fluorescence intensity was measured to determine whether MMP12 is associated with insulin and insulin-like growth factor 1 (IGF-1) in vitro. MMP12 inhibitors were used to explore whether MMP12 could affect the body weight of ApcMin/+ mice. Results MMP12 knockout led to weight gain and expansion of muscle fiber cross-sectional area (all mice had C57BL/6 background) in ApcMin/+ mice, while inhibiting MMP12 could suppress weight loss in ApcMin/+ mice. MMP12 was up-regulated in muscle tissues and peritoneal macrophages of ApcMin/+ mice. IL-6 in tumor cells and colorectal cancer patients is up-regulation. IL-6 stimulated MMP12 secretion of macrophage. Conclusions MMP12 is essential for controlling body weight of Apc Min/+ mice. Our study shows that it exists the crosstalk between cancer cells and macrophages in muscle tissues that tumor cells secrete IL-6 inducing macrophages to up-regulate MMP12. This study may provide a new perspective of MMP12 in the treatment for weight loss induced by CAC.